ICD coding changes and discontinuities in trends in cause-specific mortality in six European countries, 1950-99 - Fanny Janssen; Anton E. Kunst (The World Health Organization, 2004)
OBJECTIVE: To evaluate how often coding changes between and within revisions of the International Classification of Diseases (ICD) complicate the description of long-term trends in cause-specific mortality. METHODS: Data on cause-specific mortality between 1950 and 1999 for men and women aged 60 and older were obtained from Denmark, England and Wales, Finland, the Netherlands, Norway and Sweden. Data were obtained by five-year age groups. We constructed a concordance table using three-digit ICD codes. In addition we evaluated the occurrence of mortality discontinuities by visually inspecting cause-specific trends and country-specific background information. Evaluation was also based on quantification of the discontinuities using a Poisson regression model (including period splines). We compared the observed trends in cause-specific mortality with the trends after adjustment for the discontinuities caused by changes to coding. FINDINGS: In 45 out of 416 (10.8 %) instances of ICD revisions to cause-specific mortality codes, significant discontinuities that were regarded as being due to ICD revisions remained. The revisions from ICD-6 and ICD-7 to ICD-8 and a wide range of causes of death, with the exception of the specific cancers, were especially affected. Incidental changes in coding rules were also important causes of discontinuities in trends in cause-specific mortality, especially in England and Wales, Finland and Sweden. Adjusting for these discontinuities can lead to significant changes in trends, although these primarily affect only limited periods of time. CONCLUSION: Despite using a carefully constructed concordance table based on three-digit ICD codes, mortality discontinuities arising as a result of coding changes (both between and within revisions) can lead to substantial changes in long-term trends in cause-specific mortality. Coding changes should therefore be evaluated by researchers and, where necessary, controlled for.